The Characterization of the Olf-1/EBF-Like HLH Transcription Factor Family: Implications in Olfactory Gene Regulation and Neuronal Development - Wang, Song S. (J Neurosci, 1997)
The Olf-1/EBF helix-loop-helix (HLH) transcription factor has been implicated in olfactory gene regulation and in B-cell development. Using homology screening methods, we identified two additional Olf-1/EBF-like cDNAs from a mouse embryonic cDNA library. The Olf-1/EBF-like (O/E) proteins O/E-1, O/E-2, and O/E-3 define a family of transcription factors that share structural similarities and biochemical activities. Although these O/E genes are expressed within olfactory epithelium in an identical pattern, they exhibit different patterns of expression in the developing nervous system. Although O/E-1 mRNA is present in several tissues in addition to olfactory neurons and developing B-cells, O/E-2 and O/E-3 are expressed at high levels only in olfactory tissue. In O/E-1 knock-out animals, the presence of two additional O/E family members in olfactory neurons may provide redundancy and allow normal olfactory neurodevelopment. Further, the identification of the O/E family of HLH transcription factors and their embryonic expression patterns suggest that the O/E proteins may have a more general function in neuronal development.